Effect of fermentation methods on amino acids, fiber fractions and anti nutritional factors in different plant protein sources and essential amino acid index for Penaeus (Litopenaeus) vannamei - Jannathulla, R.; Dayal, J. Syama; Vasanthakumar, D.; Ambasankar, K.; Muralidhar, M. (Indian Journal of Fisheries, 2017)
The incorporation of plant protein sources in shrimp feed is limited due to unbalanced amino acids and higher anti-nutrients. In the present study, soybean meal (SBM), groundnut oil cake (GNC), rapeseed meal (RSM), sunflower oil cake (SFC) and guar meal (GRM) were subjected to natural, bacterial, fungal and yeast fermentation methods. The essential amino acid contents were increased by 4-28% in SBM, 7-26% in GNC, 3-27% in RSM, 8-18% in SFC and 4-14% in GRM. The increase was better for lysine with fungal fermentation (2.31-4.01%). The improvement in other limiting amino acids viz., methionine and tryptophan also showed positive response to fermentation. The analytical results showed improved essential amino acid index (EAAI) in the fermented ingredients and the increase was better with RSM (0.82 to 0.92) using Aspergillus niger. Fiber fractions were reduced (p<0.05) in fungal and yeast treated samples but not due to natural or bacterial fermentation. The reduction of cellulose and hemicellulose was not only influenced by the inoculum but also on the ingredient used. The reduction of anti-nutrients (p<0.05) such as trypsin inhibitor, phytic acid, saponin, tannin, glucosinolate and guar gum were found to be lower in natural fermentation than other methods. The results indicated that fungal fermentation is more suitable for improving the nutritional quality of plant protein sources and this data will pave way for higher fishmeal replacement in shrimp feed formulations.